The Effects of Humidity on Cast PA6G during Turning and Milling Machining - Mustafa Bozdemir (Advances in Materials Science and Engineering)
We compared the foundry PA6G samples in several dry and humid but different storage environments by processing them under the same cutting conditions such as progress rate (100, 120, 140, and 160 mm/min), cutting rate (90, 110, and 130 m/min), and cutting depth (1, 1.5, 2, 2.5, and 3 mm), in terms of formation of average surface roughness values. An improvement of 10.4% in average surface roughness was observed in the measurements performed after the milling process on the humid material and then the process was carried out under a dry condition. Degradation of about 14% in the average surface roughness was observed. The measurement was carried out after the samples were used in milling measurement which was performed on the dry PA6G material that was kept in a humid environment. An improvement of 6.4% in average surface roughness was observed. The measurements were performed after CNC machines process was applied on humid and dried PA6G material. This difference between milling and turning procedures is caused by the workpiece losing its humidity in the turning machine due to the turning effect. It was noted that the processes performed on the CNC turning stand were less affected by the humidity factor.